Distribution of pollutant in longitudinal direction of open channel flow - Saeedfar, Soheil (2012)
Predicting of distribution of pollutant in a rectangular open channel on passive mixing of pollutant in longitudinal direction is reported. A finite numerical difference scheme developed by author was extended to determine longitudinal advection and dispersion of concentration of pollutant into the open channel flow. To compute the concentration and depicting the graph versus time, modeling a channel to obtain velocity in small steps of the length of the channel was inevitable. Modeling of the channel is based on Saint-Venant equation as the governing equation. For solving the governing equations, direct numerical method by using partial differential equation into finite difference equations have been considered. In numerical method for the solution of the partial derivative equations, the computations are performed on the x-t grid depending on the length of channel. Explicit scheme for solution is considered. The unknown variables (velocity, depth, and concentration of pollutant) at a future time step t+?tare considered by a number of variables at the previous time steps. The graphs of concentration versus time and discharge versus time were depicted and compared to each other. Also the graphs of concentration with the depicted graph of experimental data were compared. Model results and field data were generally in good agreement. About 70% of the results from numerical method were matched with the data from experimental performance.